Club and Intramural Sports Participation and College Student Academic Success. Issue 1 (April 2019) - Vasold, Kerri L.; Deere, Samantha J.; Pivarnik, James M.
The purpose of this investigation was to determine the relationship between university club and intramural sports participation and student grades via the American College Health Association National College Health Assessment (NCHA) survey, while controlling for confounding variables. Data were obtained from the NCHA for the fall 2008, spring 2009, fall 2009, and fall 2010 time periods. The original sample included 178, 091 respondents. After inclusion and exclusion criteria, the final analytic sample included 85, 316 respondents. Multinomial logistic regression was used to evaluate the role of participation in club and/or intramural sports on self-reported grade averages. Analyses were adjusted for significant covariates that have been identified as potentially impacting academic success. In general, sport participants were more likely to report higher grade averages than nonparticipants. The strongest relationships were found for participants of club sports. Future research should investigate relationships between club and intramural sports and other indicators of academic success.